Treatment of Severe Hypertriglyceridemia With Insulin Infusions in Severe COVID-19: A Case Series. (December 2022) - Thomas, Caitlin M.; Vicent, Martie; Moore, Shawn; Ali, Fahd; Wooten, Leslie; Louzon, Patricia R.
Purpose: Rapid onset of severe hypertriglyceridemia was quickly recognized in critical COVID-19 patients. Associated causes have been due to secondary hemophagocytic lymphohystiocytosis (HLH) syndrome, medication-induced, or acute liver failure. Statins, omega-3 polyunsaturated acids, niacin, and fibrates are common oral lipid lowering therapy options in patients at risk for hypertriglyceridemia. The severity of hypertriglyceridemia in COVID-19 patients with triglyceride values reaching greater than 1, 000 mg/dL put them at a heightened risk of pancreatitis and therefore an essential need to acutely lower their levels. We present a case series of 5 patients who achieved rapid triglyceride lowering through continuous insulin infusion therapy. Methods: A retrospective chart review of 48 critical COVID-19 patients who were admitted from March 22 to April 15, 2020 was conducted. Inclusion criteria consisted of mechanical ventilation and continuous insulin infusion to treat severe hypertriglyceridemia resulting with 5 eligible patients in this case report. Results and Conclusion: In addition to standard oral lipid lowering therapies, continuous insulin infusion successfully treated severe hypertriglyceridemia in critically ill COVID-19 patients. None of the patients experienced pancreatitis or hypoglycemia necessitating cessation of insulin. Further studies are needed to show the optimum dose and duration of insulin infusion as monotherapy and in combination with oral therapies.